Pengaruh Audit Opinion Dan Laba Rugi Perusahaan Terhadap Audit Report Lag (Pada Perusahaan Properti & Real Estate Yang Terdaftar di Indeks Saham Syariah Indonesia Periode 2022 - 2025) - Anisa Rahayu; Mohammad Orinaldi; Faturahman (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2026)
This study aims to analyze the effect of audit opinion and company profit and loss on audit report lag in property and real estate companies listed on the Indonesian Sharia Stock Index (ISSI) during the 2022–2025 period. Audit report lag refers to the time interval between the company’s fiscal year-end and the issuance date of the independent auditor’s report. Timeliness in financial reporting is an important aspect in maintaining the relevance of information for investors and stakeholders.This study employed a quantitative method with a descriptive approach. The population consisted of all property and real estate companies listed on the ISSI during the 2022–2025 period. The sampling technique used was purposive sampling based on specific criteria, resulting in selected research samples. The data used were secondary data obtained from annual financial statements and independent auditor reports. Data analysis was conducted using panel data regression with the assistance of EViews 12 software.The results of this study indicate that audit opinion has a negative and significant effect on audit report lag. This finding shows that companies receiving an unqualified opinion tend to have a shorter audit completion time compared to companies receiving opinions other than unqualified opinions. Meanwhile, company profit and loss proxied by Net Profit Margin (NPM) does not have a significant effect on audit report lag. Simultaneously, audit opinion and company profit and loss have a significant effect on audit report lag.This study indicates that the quality of audit opinions and the company’s financial condition are important factors influencing the timeliness of financial statement audit completion. Therefore, companies are expected to improve the quality of financial reporting and strengthen internal control systems so that the audit process can be completed more effectively and efficiently.